Green Tea (EGCG) Decreases Malondialdehide In Oxidative Stress Exposure To Psychological Stress - Priaminda, M Dodi F; Wirjatmadi, Bambang; Purwanto, Bambang; Adriani, Merryana (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
-